Effects of aluminum content and mechanical nano‐alloying time on the preparation of titanium‐aluminum composite coatings on magnesium‐lithium alloy. Issue 7 (20th July 2020) - Li, Y.; Sun, J.; Zhu, X.C.; Mei, L.Y.; Lei, Y.Y.; Du, X.D.; Wu, Y.C.
Abstract: A titanium‐aluminum composite coating was successfully fabricated on magnesium‐lithium alloy substrate by mechanical nano‐alloying treatment (SMNAT). The effects of aluminum content and mechanical nano‐alloying time on the microstructure and properties of titanium‐aluminum composite coatings were investigated. The experimental results showed that the ratio of titanium‐aluminum powder has a significant effect on the preparation of the coating. Low aluminum content and high aluminum content in the mixture powder resulted in the formation of the coatings with inhomogeneous thickness. The titanium‐aluminum ratio of 3 : 1 was considered to be optimal for fabricating the coating with homogeneous thickness under the selected milling parameters. The hardness of top surface layer on titanium‐ aluminum coatings decreased from 292.0 HV 0.01 to 121.4 HV 0.01 with the increase of aluminum content. Additionally, the prolongation of treatment time facilitated to increase the thickness and density of the coatings, resulting to enhance their hardness and corrosion resistance. Abstract : Through the research of effects of aluminum content and mechanical nano‐alloying time on the preparation of titanium‐aluminum composite coatings on magnesium‐lithium alloy, the proper amount of aluminum powder with the appropriate milling time can fabricate the coating with continuous and uniform thickness.